Pharmacokinetics and Dosing of Levofloxacin in Children Treated for Active or Latent Multidrug-resistant Tuberculosis, Federated States of Micronesia and Republic of the Marshall Islands. Issue 4 (April 2016) - Mase, Sundari R.; Jereb, John A.; Gonzalez, Daniel; Martin, Fatma; Daley, Charles L.; Fred, Dorina; Loeffler, Ann M.; Menon, Lakshmy R.; Bamrah Morris, Sapna; Brostrom, Richard; Chorba, Terence; Peloquin, Charles A.
Abstract : Background: In the Federated States of Micronesia and then the Republic of the Marshall Islands (RMI), levofloxacin pharmacokinetics were studied in children receiving directly observed once-daily regimens (10 mg/kg, age >5 years; 15–20 mg/kg, age ⩽5 years) for either multidrug-resistant tuberculosis disease or latent infection after multidrug-resistant tuberculosis exposure, to inform future dosing strategies. Methods: Blood samples were collected at 0 (RMI only), 1, 2 and 6 hours (50 children, aged 6 months to 15 years) after oral levofloxacin at >6 weeks of treatment. Clinical characteristics and maximal drug concentration (Cmax ) of levofloxacin, elimination half-life and area under the curve from 0 to 24 hours (AUC0–24 hours × μg/mL) were correlated to determine the optimal dosage and to examine associations. Population pharmacokinetics and target attainment were modeled. With results from the Federated States of Micronesia, dosages were increased in RMI toward the target Cmax for Mycobacterium tuberculosis, 8–12 µg/mL. Results: Cmax correlated linearly with per-weight dosage. Neither Cmax nor half-life was associated with gender, age, body mass index, concurrent medications or predose meals. At levofloxacin dosage of 15–20 mg/kg, Cmax ≥8 µg/mL was observed, and modeling corroborated a high target attainment across the ratio of the area under the free concentration versus time curve to minimum inhibitory concentration ( f AUCss, 0–24 /MIC) values. Conclusions: Levofloxacin dosage should be 15–20 mg/kg for Cmax ≥8 µg/mL and a high target attainment across f AUCss, 0–24 /MIC values in children ≥2 years of age. Abstract : Supplemental Digital Content is available in the text.